Anti-hypertensive treatment in peripheral artery disease. (April 2018) - Tsioufis, Costas; Andrikou, Ioannis; Siasos, Gerasimos; Filis, Konstantinos; Tousoulis, Dimitrios
Graphical abstract: Highlights: A blood pressure goal of less than 130/80 mmHg is recommended in PAD. All classes of antihypertensive medication are equal. BBs are not contraindicated. In carotid atherosclerosis, CCBs and ACEIs are recommended. In renal artery disease treatment includes RAS inhibitors, CCBs, BBs, diuretics. In renal artery disease, interventional treatment vs medication is a debated issue. Abstract : Peripheral artery disease (PAD) affects more than 200 million people worldwide. Hypertension has been related to increased risk of PAD. The treatment of elevated blood pressure (BP) in these patients is indicated to lower the cardiovascular risk with a BP goal of less than 130/80 mmHg. Although there is no evidence that one class of antihypertensive medication or strategy is superior for BP lowering in PAD, the use of renin-angiotensin-system (RAS) inhibitors can be effective to reduce the cardiovascular risk. Beta-blockers (BBs) are not contraindicated. In the presence of carotid atherosclerosis, calcium-channel blockers (CCBs) and angiotensin-converting-enzyme inhibitors are recommended. In fibromuscular dysplasia the treatment of choice is percutaneous renal angioplasty. In renal artery disease optimal medical therapy includes RAS inhibitors, CCBs, BBs and diuretics.